Callogobius falx, a new species of goby from southern Japan - Fujiwara, Kyoji; Suzuki, Toshiyuki; Motomura, Hiroyuki (Zootaxa, 2021)
Callogobius falx n. sp. (Gobiidae) is described on the basis of two specimens (14.4 and 23.1 mm in standard length: SL) from the Ryukyu Islands, southern Japan. The new species is characterized by the following combination of characters: dorsal-fin rays VI-I, 8 or 9; anal-fin rays I, 7; pectoral-fin rays 18 or 19; lateral scale rows 20–22; body depth moderate, neither particularly slender nor deep (depth at pelvic-fin origin 18.3–20.0% of SL); pelvic-fin base with frenum; caudal-fin length moderate, margin rounded; cephalic sensory-canal pores absent; interorbital papillae row separated, forming two rows (one row in 14.4 mm paratype); postorbital papillae row not continuous with upper cranial papillae row; preopercular and transverse opercular papillae rows connected, forming single transverse row; body with three oblique black bars, angled upwards anteriorly and continuous with black bars on dorsal fins, anteriormost bar extending from 1st dorsal fin to midline of body, posterior two bars extending from second dorsal fin to dorsal surface of body and caudal peduncle, respectively; pectoral fin white, upper half widely (ca. 1/2 length of rays) margined with black; caudal-fin base with narrow sickle-like bar.